PERSPECTIVE DIRECTION OF MODEM METALLURGY - CHLORIDE M ETALLURGY - P. A. Kovgan; M. G. Abuov; A. I. Edilbaev; A. N. Zadiranov (Литьë и металлургия)
Principally new perspective direction in metallurgy - chloric metallurgy is examined.